Diagnosis and Management of Graves' Disease in Thailand: A Survey of Current Practice. (11th May 2020) - Sriphrapradang, Chutintorn
Abstract : Background . The data on clinical practice patterns in the evaluation and management of Graves' disease (GD) are limited in Asia. The aims of this survey were to report the current practices in the management of GD in Thailand and to examine any international differences in the management of GD. Methods . Members of the Endocrine Society of Thailand who were board certified in endocrinology ( N  = 392) were invited to participate in an electronic survey on the management of GD using the same index case and questionnaire as in previous North American and European surveys. Results . One hundred and twenty responses (30.6%) from members were included. TSH receptor antibody measurement (29.2%), thyroid ultrasound (6.7%), and isotopic studies (5.9%) were used less frequently to confirm the etiology compared with those in North American and European surveys. Treatment with an antithyroid drug (ATD) was the preferred first choice of therapy (90.8%). Methimazole at 10–15 mg/day with a beta-blocker was the initial treatment of choice. The preferred ATD in pregnancy was propylthiouracil in the first trimester and methimazole in the second and third trimesters, which was similar to the North American and European surveys. Conclusion . Ultrasound and isotopic studies will be requested only by a small proportion of Thai endocrinologists. Higher physician preference for ATD is similar to Europe, Latin America, and other Asian countries. Geographical differences in the use of ATD, radioactive iodine, and thyroidectomy exist.